Wiring and Rewiring of the Retinogeniculate Synapse - Hong, Y. Kate (2011)
The formation and refinement of synaptic circuits are areas of research that have fascinated neurobiologists for decades. A recurrent theme seen at many CNS synapses is that neuronal connections are at first imprecise, but refine and can be rearranged with time or with experience. Today, with the advent of new technologies to map and monitor neuronal circuits, it is worthwhile to revisit a powerful experimental model for examining the development and plasticity of synaptic circuits-the retinogeniculate synapse.